The GREEN resource : the development of leadership capacity in higher education. - Lefoe, Geraldine; Parrish, Dominique; Smigiel, Heather; Albury, Rebecca (University of Wollongong, Centre for Educational Development and Interactive Resources, 2008)
Resource emanating from a project that investigated the development and trial of a Leadership Capacity Development Framework (LCDF) for teaching and learning in higher education. Four Australian universities were involved in the project, which assessed the relevance and validity of the LCDF in developing leadership capacity. The project found that: distributive leadership is most successful if the leadership roles and responsibilities are negotiated rather than delegated; distributive leadership harnesses individual strengths and abilities appropriate for the required leadership, irrespective of formal position. A distributive approach provides an opportunity to take a leadership role, ascertain capability, and further develop these aptitudes before acquiring a formal position. This resource provides details of the five domains - growing, reflecting, enabling, engaging and networking, and also describes associated practical activities facilitated throughout the project.